Single nucleotide variants in the CCL2, OAS1 and DPP9 genes and their association with the severity of COVID-19 in an Ecuadorian population - Chávez-Vélez, Erik; Álvarez-Nava, Francisco; Torres-Vinueza, Alisson; Balarezo-Díaz, Thalía; Pilataxi, Kathya; Acosta-López, Camila; Peña, Ivonne Z.; Narváez, Katherin (Frontiers in Cellular and Infection Microbiology, 2024)
COVID-19 has a broad clinical spectrum, ranging from asymptomatic-mild form to severe phenotype. The severity of COVID-19 is a complex trait influenced by various genetic and environmental factors. Ethnic differences have been observed in relation to COVID-19 severity during the pandemic. It is currently unknown whether genetic variations may contribute to the increased risk of severity observed in Latin-American individuals The aim of this study is to investigate the potential correlation between gene variants at CCL2, OAS1, and DPP9 genes and the severity of COVID-19 in a population from Quito, Ecuador.